New essays on the Catcher in the Rye - Salzman, Jack (The American novel, 1991)
First published in 1951, Catcher in the Rye continues to be one of the most popular novels ever written as well as one of the most frequently banned books in the United States. In his introduction to this volume, Jack Salzman discusses the history of the novel's composition and publication, the mixed reception it received from critics and scholars, the arguments surrounding the attempts at censorship, and its position in a postmodernist literary world. The five essays that follow focus on various aspects of the novel: its ideology within the context of the Cold War, its portrait of a particular subculture within American society, its account of patterns of adolescent crisis, and its rich and complex narrative structure